Planing effective instruction: diversity responsive methods and management - Karna L. Nelson; Price, Kay (Wadsworth, 2011)
Contiene: thinking about content. Writing objectives. General aprproaches to universal instructional interventions. Critical teaching skill for focusing attention. Critical teaching skill for plannining practice and monitoring student progress. Critical teaching skill for plannining patner and small - group work. Selected instructional interventions.